Geography for Children: Drawing and Spatial Thinking - Juliasz, Paula Cristiane Strina (Journal of Geography Education, 2022)
Spatial representations are part of the cartographic and geographic literacy process. This paper aims to analyze drawing as a representation system, a language to communicate spatial thinking based on the relationship between thought and language under the historical cultural theory. Three main points are addressed herein: spatial thinking and Geography in primary school; the relation between experience, everyday life, and spatial thinking; and spatial representation through drawing. Drawings by preschool students are presented as a way of broadening spatial thinking and part of the cartographic literacy process. The idea that geographic education creates conditions to disrupt pre-established views of everyday life is the central axis of this research.